2019
DOI: 10.7883/yoken.jjid.2018.222
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of Tetanus Seropositivity Levels in Different Age Groups in Ankara Province, Turkey, 2017

Abstract: The aim of this research is to determine the seropositivity levels of tetanus vaccine according to age groups in Ankara province, to identify possible factors that could affect the immune status, and to make recommendations especially in people aged 50 years and older. This cross-sectional epidemiological study covers people over three years of age registered in the Family Medicine Information System. We received blood samples from 992 people and 968 of them were surveyed. Protective tetanus antibody levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…Similar comments were made in some studies where protection was found to be higher. Looking at the studies in Turkey, it was reported in a study conducted with people age range 3-104 years in Ankara that protective tetanus antibody levels were found in 45.2% of females and in 54.8% of males (13). There were no significant differences between males and females in terms of protectiveness in other studies conducted in Turkey (8,(13)(14)(15).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Similar comments were made in some studies where protection was found to be higher. Looking at the studies in Turkey, it was reported in a study conducted with people age range 3-104 years in Ankara that protective tetanus antibody levels were found in 45.2% of females and in 54.8% of males (13). There were no significant differences between males and females in terms of protectiveness in other studies conducted in Turkey (8,(13)(14)(15).…”
Section: Resultsmentioning
confidence: 95%
“…Looking at the studies in Turkey, it was reported in a study conducted with people age range 3-104 years in Ankara that protective tetanus antibody levels were found in 45.2% of females and in 54.8% of males (13). There were no significant differences between males and females in terms of protectiveness in other studies conducted in Turkey (8,(13)(14)(15). Looking at the examples from the world, it was found that 37% of men and 64% of women were below the protective level of antibody titers in a study conducted in a 30-70 age group in Denmark (9).…”
Section: Resultsmentioning
confidence: 95%
“…In adults with unknown or incomplete primary vaccination, primary vaccination program should be started and should be completed. 11 In the studies performed, the levels of protective antibodies against tetanus were found to be sufficient in children and adolescents; whereas in 50% of patients over the age of 40, protective antibody titer against tetanus had been found to be insufficient. 5,13,14 In a recent study in our country; sufficient tetanus antibody was detected in 140 (39.…”
Section: Discussionmentioning
confidence: 93%
“…In adults with unknown or incomplete primary vaccination, primary vaccination program should be started and should be completed. 11 In the studies performed, the levels of protective antibodies against tetanus were found to be sufficient in children and adolescents; whereas in 50% of patients over the age of 40, protective antibody titer against tetanus had been found to be insufficient. 5,13,14 17 In order to reach the targeted vaccination rates, the society should be informed about tetanus and vaccination to be protected from tetanus and ensuring sustainability of immunization in individuals with appropriate vaccination programs is the most important step.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation